A CUTANEOUS ADVERSE EFFECTS IN COVID-19 VACCINE - Betsy Yosia Nadeak; Keneyzia Carla Gliselda; Larasati Budiyarto; Fredric Zulkifly (Faculty of Medicine Universitas Mataram, 2022)
In March 2020, the World Health Organization (WHO) declared COVID-19 as a Pandemic. Vaccines are biological products that can be used to induce the body's immune response which can provide protection against infection and/or disease upon exposure to pathogens. As such, vaccination becomes one of the key roles to prevent the spreading of COVID-19. Based on the results of clinical trials, COVID-19 vaccine shows adequate levels of immunogenicity with various levels of effectiveness and acceptable level of safety. With vaccinations being implemented worldwide, side effects ranging from mild to severe have been reported. Understanding mucocutaneousside effects of COVID-19 Vaccine are important, as they can be seen with the naked eye and have the potential to frighten individuals and populations, leading to public reluctance to being vaccinated.